Rationally Engineered AAV Capsids Improve Transduction and Volumetric Spread in the CNS - Nicholas M. Kanaan; Rhyomi C. Sellnow; Sanford L. Boye; Ben Coberly; Antonette Bennett; Mavis Agbandje-McKenna; Caryl E. Sortwell; William W. Hauswirth; Shannon E. Boye; Fredric P. Manfredsson (Elsevier, 2017)
Adeno-associated virus (AAV) is the most common vector for clinical gene therapy of the CNS. This popularity originates from a high safety record and the longevity of transgene expression in neurons. Nevertheless, clinical efficacy for CNS indications is lacking, and one reason for this is the relatively limited spread and transduction efficacy in large regions of the human brain. Using rationally designed modifications of the capsid, novel AAV capsids have been generated that improve intracellular processing and result in increased transgene expression. Here, we sought to improve AAV-mediated neuronal transduction to minimize the existing limitations of CNS gene therapy. We investigated the efficacy of CNS transduction using a variety of tyrosine and threonine capsid mutants based on AAV2, AAV5, and AAV8 capsids, as well as AAV2 mutants incapable of binding heparan sulfate (HS). We found that mutating several tyrosine residues on the AAV2 capsid significantly enhanced neuronal transduction in the striatum and hippocampus, and the ablation of HS binding also increased the volumetric spread of the vector. Interestingly, the analogous tyrosine substitutions on AAV5 and AAV8 capsids did not improve the efficacy of these serotypes. Our results demonstrate that the efficacy of CNS gene transfer can be significantly improved with minor changes to the AAV capsid and that the effect is serotype specific. Keywords: AAV, CNS, capsid, mutant